2013
DOI: 10.1186/1750-1172-8-99
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm to predict phenotypic severity in mucopolysaccharidosis type I in the first month of life

Abstract: IntroductionMucopolysaccharidosis type I (MPS I) is a progressive multisystem lysosomal storage disease caused by deficiency of the enzyme α-L-iduronidase (IDUA). Patients present with a continuous spectrum of disease severity, and the most severely affected patients (Hurler phenotype; MPS I-H) develop progressive cognitive impairment. The treatment of choice for MPS I-H patients is haematopoietic stem cell transplantation, while patients with the more attenuated phenotypes benefit from enzyme replacement ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 54 publications
0
42
0
4
Order By: Relevance
“…Such cases could be closely monitored and proceed to HCT as soon as a severe phenotype is suggested. 25 An international expert consensus statement is important for further recommendations. Furthermore, considering the higher and more stable IDUA enzyme levels achieved after HCT, one might argue that patients with MPS type I with a more attenuated phenotype (MPS I Hurler-Scheie) are better off with HCT compared with ERT, 4 especially as HCT has become much safer in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases could be closely monitored and proceed to HCT as soon as a severe phenotype is suggested. 25 An international expert consensus statement is important for further recommendations. Furthermore, considering the higher and more stable IDUA enzyme levels achieved after HCT, one might argue that patients with MPS type I with a more attenuated phenotype (MPS I Hurler-Scheie) are better off with HCT compared with ERT, 4 especially as HCT has become much safer in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…HS levels were determined as described previously (Kingma et al 2013). HS in 25 μg of fibroblast lysate was enzymatically digested into disaccharides.…”
Section: Methodsmentioning
confidence: 99%
“…26 These studies require long-term fibroblast cultures and mass spectrometry-based GAG assays. Kingma et al 27 developed an algorithm to predict clinical severity in MPS I based on genotyping and an optimized IDUA assay, however, this assay is not routinely available. In a preliminary proteomic study, the lysosomal protein b-galactosidase was elevated 3.6-to 5.7-fold in severe but not attenuated MPS I, 28 and 1 study has reported that serum heparin-cofactor IIthrombin complex levels can differentiate patients with severe MPS I from patients with attenuated MPS I.…”
Section: Lack Of Routine Biochemical Markersmentioning
confidence: 99%